PENIGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA MELALUI MODEL PEMBELAJARAN KOOPERATVE TIPE TGT DI SMAN 1 BATANG TORU - Uli Tamana Pardede (JURNAL MathEdu (Mathematic Education Journal), 2019)
This study aims to increase students’ critical thinking ability through TGT (Teams Game Tournament) learning model at the tenth grade students of SMAN 1 Batangtoru. The research was conducted by applying Class Action Research (CAR) for 3 months (June–August 2018) with 30 students as the object. The research consists of two cycles. The first cycle showed the average of students’ critical thinking ability was 73.42 (classical mastery of 43.33%) and research was continued to the second cycle. The second cycle showed the average of students’ critical thinking ability was 83.16 (classical mastery of 90%). It’s concluded TGT learning model able to improve students’ critical thinking at the tenth grade students of SMAN 1 Batangtoru. Keywords: improve, TGT learning model, critical thinking ability